Wisdom and the Sages in the Quran - Muhammadriza Mustafapur (حکمت اسرا, 2010)
Wisdom is a divine gift granted to whosoever God wants. If a person acquires the reality of wisdom, which is informed by sound understanding and correct action, he has come by a ‘great good’ indeed. As the bestowal of wisdom on behalf of God is not a vain act, it stands to reason that the recipients of wisdom should strive to prepare the grounds and acquire the capacity to receive the same. Hence, it is the prophets and the saints, as well as their followers, who are worthy enough and who have the aptitude of wisdom.